PADI ORGANIK VERSUS NON ORGANIK: STUDI FISIOLOGI BENIH PADI (Oryza sativa L.) KULTIVAR LOKAL ROJOLELE - Dody Priadi; Tatang Kuswara; Usep Soetisna (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2007)
Study of the effect of organic and non-organic farming practice of rice (Oryza sativa L.) cv. Rojolele on seed physiology was carried out in Cipanas, West Java (on-farm) and in the laboratory of BSJ3 and greenhouse of RC for Biotechnology  (off-farm). Parameters were recorded particularly on seed germination percentage, water content, dormancy behavior and morphology. On-farm study results showed that germination percentage of organic seeds was higher (88.3% at water content of 13.4%) than those non-organic seeds (20.0% at water content of 10.2%). Results of off-farm study showed that the plant height of those organic seeds was higher than those non-organic seeds. On-farm practice the harvest after 150 days showed that the non-organic seeds produced more yellow grains (44.8%) than those of organic seeds (39.6%). A total grain per plant produced by the non-organic seeds was higher than those organic seeds, however, total percentage of the filled out organic seeds was higher (57.8%) than those non-organic seeds (40.1%). Organic seeds seem to be more dormant than those non-organic seeds after storage for 12 months. Grain weight of both non-organic and organic was 17-19 g per 1000 seeds. Germination of off-farm non-organic seeds was 98.0%, whereas those organic seeds were 95.0% at water content of 10.8% respectively. In view of seed physiology, organic rice quality better than those non- organic because they contain more filled out seeds, even though the organic rice harvesting time longer than those non-organic. Although off-farm study represented seed physiology of either organic or non-organic seeds, on-farm study needs to be further done on all aspects of seed physiology.